Identification and Inventory of Customary (Ulayat) Land among the Pakpak Indigenous Community in Dairi and Pakpak Bharat Regencies - Andi Nova Bukit, SH., MH; Boy Laksamana, SH., M.Hum; Afrita, SH., M.Hum; D. Shahreiza, SH., MH (Universitas Sumatera Utara, 2026)
This study examines the role and function of customary legal structures within the Pakpak Indigenous Community, with particular attention to the preservation of customary norms related to communal land rights, inheritance, marriage, and kinship systems. The research focuses on Sulang Silima, the highest customary legal authority among the Pakpak people, which holds jurisdiction in establishing, interpreting, and enforcing customary norms governing social and legal relations within the community. This study employs a qualitative ethnographic approach to obtain an in-depth understanding of how customary law operates as a living legal system within the Pakpak Indigenous Community. Through field observation and qualitative analysis, the research explores how the institutional structure of Sulang Silima regulates internal governance and decision-making processes, particularly in matters concerning customary land transactions, inheritance arrangements, and kinship obligations. The findings reveal that Sulang Silima functions as a central normative institution that maintains social order and safeguards the collective rights of the Pakpak Indigenous Community. In practice, a customary leader (kepala adat) may be appointed from the same clan to serve as an intermediary between the community and the five elements of Sulang Silima; however, the kepala adat does not possess decision-making authority within the customary legal framework and performs primarily ceremonial functions. Furthermore, customary mechanisms such as pago-pago and ajeg-ajeg play a significant role in legitimizing customary land transactions through communal deliberation and ritual validation. The study concludes that the continued existence of Sulang Silima demonstrates the enduring relevance of indigenous legal systems within Indonesia’s pluralistic legal order. Recognition and protection of customary institutions and communal land rights are therefore essential for ensuring legal certainty, safeguarding indigenous identity, and promoting equitable and sustainable development within the national legal framework.